Book Scavenger - Bertman, Jennifer Chambliss (Bertman, Jennifer Chambliss. Book scavenger, 2015)
Twelve-year-old Emily is on the move again. Her family is relocating to San Francisco, home of her literary idol: Garrison Griswold, creator of the online sensation Book Scavenger, a game where books are hidden all over the country and clues to find them are revealed through puzzles. But Emily soon learns that Griswold has been attacked and is in a coma, and no one knows anything about the epic new game he had been poised to launch. Then Emily and her new friend James discover an odd book, which they come to believe is from Griswold and leads to a valuable prize. But there are others on the hunt for this special book, and Emily and James must race to solve the puzzles Griswold left behind before his attackers come after them.